Efeito da infusão ruminal de amônia sobre o aproveitamento de feno do capim-buffel para caprinos - Lopes, Angélica Soares de Mendonça (2018)
The objective of this study was to evaluate the effects of supplementation with non-protein nitrogen (NNP) on the intake, digestibility, ruminal parameters and nitrogen balance of goats fed buffelgrass hay. Five goats with no defined racial pattern (NDRP), adults, castrated and cannulated in the rumen were used, with an average weight of 45 ± 2,3 kg. Five diets were provided, where the control treatment consisted only of buffelgrass hay feeding with 5.5% crude protein (CP) based on dry matter (DM), supplied ad libitum, while the other treatments treatments of the addition of increasing levels of nitrogen supplements via ruminal infusion, aiming at the gradual increase of ruminal ammonia concentration (N-NH3). Thus the concentrations were 3.43; 9.95; 17.18; 23.02; and 33.68 mg / dL of N-NH3 in ruminal fluid. The supplement provided was a mixture of urea, ammonium sulfate and casein, in ratios of 75: 8.33: 16.67, respectively. There was a quadratic (P <0.05) effect of N-NH3 concentration on DM, neutral detergent fiber (NDF), non-fibrous carbohydrates (NFC) and total carbohydrate (TCHO) levels with maximum responses on the levels of 14.48 mg / dL, 13.72 mg / dL, 13.77 mg / dL, 13.76 mg / dL N-NH3, respectively. The digestibility coefficients of DM, NDF TCHO, NFC were not affected by supplementation (P> 0.05). However, there was an increasing linear effect (P <0.05) on the digestibility of ethereal extract (EE) and CP. The pH of the ruminal liquid was not influenced (P> 0.05) by the inclusion of the nitrogen supplement, with a mean value of 6.43. Ammonia nitrogen (N-NH3) was influenced by supplementation, presenting increasing linear behavior (P <0.05). The contents of rumen acetate, propionate, butyrate and total short chain fatty acids were not influenced by supplementation (P> 0.05). There was an increasing linear effect of supplementation in relation to nitrogen intake (NC) and nitrogen excretion in urine (NU) (P <0.05). Ammonia nitrogen concentrations of 3.42 and 14.48 mg / dL are sufficient to provide nitrogen substrates necessary to maintain microbial activity in the rumen and maximize voluntary buffel hay intake by goats, respectively.